Induction of nuclear factor-κB signal-mediated apoptosis and autophagy by reactive oxygen species is associated with hydrogen peroxide-impaired growth performance of broilers. (3rd May 2018) - Chen, X.; Gu, R.; Zhang, L.; Li, J.; Jiang, Y.; Zhou, G.; Gao, F.
Abstract : The oxidative study has always been particularly topical in poultry science. However, little information about the occurrence of cellular apoptosis and autophagy through the reactive oxygen species (ROS) generation in nuclear factor- κ B (NF- κ B) signal pathway was reported in the liver of broilers exposed to hydrogen peroxide (H2 O2 ). So we investigated the change of growth performance of broilers exposed to H2 O2 and further explored the occurrence of apoptosis and autophagy, as well as the expression of NF- κ B in these signaling pathways in the liver. A total of 320 1-day-old Arbor Acres male broiler chickens were raised on a basal diet and randomly divided into five treatments which were arranged as non-injected treatment (Control), physiological saline (0.75%) injected treatment (Saline) and H2 O2 treatments (H2 O2(0.74), H2 O2(1.48) and H2 O2(2.96) ) received an intraperitoneal injection of H2 O2 with 0.74, 1.48 and 2.96 mM/kg BW. The results showed that compared to those in the control and saline treatments, 2.96 mM/kg BW H2 O2 -treated broilers exhibited significantly higher feed/gain ratio at 22 to 42 days and 1 to 42 days, ROS formation, the contents of oxidation products, the mRNA expressions of caspases (3, 6, 8), microtubule-associated protein 1 light chain 3 (LC3)-II/LC3-I, autophagy-related gene 6, Bcl-2 associated X and protein expressions of total caspase-3 and total LC3-II, and significantly lower BW gain at 22 to 42 days and 1 to 42 days, the activities of total superoxide dismutase and glutathione peroxidase, the expression of NF- κ B in the liver. Meanwhile, significantly higher feed/gain ratio at 1 to 42 days, ROS formation, the contents of protein carbonyl and malondialdehyde, the mRNA expression of caspase-3 and the protein expressions of total caspase-3 and total LC3-II, as well as significantly lower BW gain at 22 to 42 days and 1 to 42 days were observed in broilers received 1.48 mM/kg BW H2 O2 treatment than those in control and saline treatments. These results indicated that oxidative stress induced by H2 O2 had a negative effect on histomorphology and redox status in the liver of broilers, which was associated with a decline in growth performance of broilers. This may attribute to apoptosis and autophagy processes triggered by excessive ROS that suppress the NF- κ B signaling pathway.